Surgical repair of ruptured sinus of Valsalva aneurysm: 13‐year single center experience. Issue 4 (21st January 2021) - Jaswal, Vivek; Kumar, Vikas; Thingnam, Shyam K. S.; Puri, Goverdhan D.
Abstract: Background and Aim: Untreated ruptured sinus of Valsalva aneurysms ultimately develop into heart failure, thereby affecting patients' survival. We retrospectively analyzed our 13‐year experience of the surgical repair for ruptured sinus of Valsalva aneurysm to study the optimal surgical strategy, operative risk and long‐term surgical outcome. Methods: Twenty‐six patients underwent surgical repair of ruptured sinus of Valsalva aneurysm from January 2008 to February 2020. Follow‐up data were obtained from the outpatient department records and telephone calls. Results: Patch closure of ruptured sinus of Valsalva aneurysm was done in all the 26 patients, most often through the transaortic (69%) and dual‐chamber approach (23%). Aortic valve repair was done in one patient while seven patients underwent aortic valve replacement for associated significant aortic regurgitation. There was one in‐hospital mortality because of noncardiac cause. The median duration of postoperative hospital stay was 8 days (range, 6–11 days). Follow‐up data were available for 89% (23/26) patients. The mean follow‐up period was 69 ± 43 months (range, 7–147 months). All survivors were in New York Heart Association functional Class I or II. There was no late death. One patient required rehospitalization for recurrent ruptured sinus of Valsalva aneurysm. There was no recurrent or new‐onset significant aortic regurgitation and prosthesis‐related complications in late follow‐up. Conclusion: Surgical repair for ruptured sinus of Valsalva aneurysm carries an acceptable low operative risk and excellent long‐term outcome. Though high‐risk population, an early diagnosis and optimal surgical approach can prevent worsening of symptoms and consequent heart failure.